2020
DOI: 10.1038/s41598-020-73582-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonically enhanced mid-IR light source based on tunable spectrally and directionally selective thermal emission from nanopatterned graphene

Abstract: We present a proof of concept for a spectrally selective thermal mid-IR source based on nanopatterned graphene (NPG) with a typical mobility of CVD-grown graphene (up to 3000 $$\hbox {cm}^2\,\hbox {V}^{-1}\,\hbox {s}^{-1}$$ cm 2 V - 1 s - 1 ), ensuring scalability to large areas. For that, we solve the electrostatic problem of a conducting hyperboloid with an elliptical wormhole in the presence of an in-plane electric field. The localized surface plasmons (LSPs) on the NPG sheet, partially hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Compared to Si 3 N 4 and standard SiO 2 , the electron migration rate in graphene is reduced due to the introduction of additional scattering centers. This method is optional for controlling the concentration and polarity of carriers in graphene and provides conditions for the manufacture of devices with complementary phenomenon, access zones or high conductivity channels, low resistance at contact or low carrier density [3].…”
Section: Graphene Edmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to Si 3 N 4 and standard SiO 2 , the electron migration rate in graphene is reduced due to the introduction of additional scattering centers. This method is optional for controlling the concentration and polarity of carriers in graphene and provides conditions for the manufacture of devices with complementary phenomenon, access zones or high conductivity channels, low resistance at contact or low carrier density [3].…”
Section: Graphene Edmentioning
confidence: 99%
“…These methods include devices, such as Graphene ED [3], SB-MOSFETs, reconfigurable FET [2], FD semiconductor and 2D materials [4], and electron-hole bilayer (EHB)-based TFET [5]. At the same time, the system on ED has been built, which has not been implemented.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction is so weak that the IMT cannot be achieved. That is why in the wavelength regime of 8–12 μm the photodetection is based purely on the bolometric effect in the semiconducting phase of VO 2 . , VO 2 -based heterostructures have shown an improvement in photoresponse in the visible and ultraviolet regions. Here, by adding a single layer of nanopatterned graphene (NPG) on top of a layer of VO 2 , we present the model of a photodetector that not only greatly enhances the absorption of mid-IR light energy in the longer wavelength regime from λ = 6 μm and exceeding 12 μm but also narrows the absorption bandwidth to 0.1 μm within the mid-IR range of 3–12 μm, thereby enabling plasmonically enhanced spectrally selective absorption of mid-IR light for the IMT effect in a heterostructure made of NPG and VO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the weak absorbance of pristine graphene of around 2%, we created nanopatterned CVD-grown single-layer graphene (NPG) that exhibits absorbance exceeding 60% in the long-wavelength infrared (LWIR) regime between λ = 8 and 12 μm. , Recently, we showed that NPG with smaller sizes of hexagonally arranged holes and smaller lattice constants exhibits absorbance of 80% in the mid-wavelength (MWIR) regime between λ = 3 and 8 μm . Because of the resolution limit of e-beam lithogaphic systems it is currently impossible to create smaller nanopatterns for increasing the absorbance of NPG at shorter wavelengths.…”
mentioning
confidence: 99%
“…1,2 Recently, we showed that NPG with smaller sizes of hexagonally arranged holes and smaller lattice constants exhibits absorbance of 80% in the midwavelength (MWIR) regime between λ = 3 and 8 μm. 3 Because of the resolution limit of e-beam lithogaphic systems it is currently impossible to create smaller nanopatterns for increasing the absorbance of NPG at shorter wavelengths.…”
mentioning
confidence: 99%